A commentary on the Council of Europe Convention on Action against Trafficking in Human Beings - Planitzer, Julia; Sax, Helmut (Elgar commentaries, 2020)
"This comprehensive Commentary provides the first fully up-to-date analysis and interpretation of the Council of Europe Convention on Action against Trafficking in Human Beings. It offers a concise yet thorough article-by-article guide to the Convention's anti-trafficking standards and corresponding human rights obligations. This Commentary includes an analysis of each article's drafting history, alongside a contextualisation of its provisions with other anti-trafficking standards and a discussion of the core issues of interpretation. The Commentary also presents the first full exploration of the findings of the Convention's monitoring body, the Group of Experts on Action against Trafficking in Human Beings (GRETA), providing a better understanding of the practical implications and challenges in relation to the Convention's standards. Practitioners in the field of anti-trafficking, including lawyers, law enforcement agencies and providers of victim support services will find the Commentary's concise analysis invaluable. It will also prove useful to researchers and students of human rights law, as well as to policymakers looking for guidance concerning obligations stemming from the Convention"--